2021
DOI: 10.1055/a-1388-7950
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Chest CT for Differentiating COVID-19 from COVID-19 Mimics

Abstract: Purpose To determine the performance of radiologists with different levels of expertise regarding the differentiation of COVID-19 from other atypical pneumonias. Chest CT to identify patients suffering from COVID-19 has been reported to be limited by its low specificity for distinguishing COVID-19 from other atypical pneumonias (“COVID-19 mimics”). Meanwhile, the understanding of the morphologic patterns of COVID-19 has improved and they appear to be fairly specific. Materials and Methods Between 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…Although there are studies that may suggest otherwise [8], it is generally expected that accurate diagnosis rates will improve with increased professional experience. However, professional experience alone is not enough for the radiological evaluation to be accurate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are studies that may suggest otherwise [8], it is generally expected that accurate diagnosis rates will improve with increased professional experience. However, professional experience alone is not enough for the radiological evaluation to be accurate.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, during the evaluation, junior residents showed a tendency to diagnose COVID-19, a condition they frequently encountered in daily practice. Another study conducted among radiology physicians (specialists and residents) in the early period of COVID-19 showed that radiologists, even without knowing the patient's clinic, were able to distinguish the diagnosis of COVID-19 with thoracic CT from other viral agents, independent of their professional experience [8]. As professional experience increases, so does self-confidence in decisions [5].…”
Section: Discussionmentioning
confidence: 99%
“…Datenitems aus dieser initialen Datenerhebung im Netzwerk bereit. Hierzu wurden internationale und nationale Standards wie CO-RADS [ 14 ], COV-RADS [ 15 ], die Empfehlung der Arbeitsgruppe Thorax der Deutschen Röntgengesellschaft [ 16 ] und weitere aufgegriffen sowie auch neue radiologische Befundungsstandards abgestimmt. RACOON erlaubt hochqualitative strukturierte Auswertungen multimodaler Datensätze im multizentrischen Setting.…”
Section: Die Fünf Komponenten Der Num-forschungsdateninfrastrukturunclassified
“…1. Until now, these findings have been considered well understood and present in the vast majority of patients with confirmed SARS-CoV-2 pneumonia [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%